Renal insufficiency caused by TMEM216 gene mutation: Case Report - Lingjun Sun; Meiqi Xu; Xiaoying Deng; Xiaoyan Liu (Frontiers in Medicine)
IntroductionChronic kidney disease (CKD) is a globally prevalent condition characterized by high morbidity and a progressive course that often culminates in end-stage renal disease (ESRD), necessitating dialysis or kidney transplantation. In recent years, genetic factors have received increasing attention in the pathogenesis of CKD, particularly among patients with unexplained renal dysfunction. Genetic screening has emerged as a valuable diagnostic tool. Mutations in the TMEM216 gene, a pathogenic variant associated with ciliopathy, have been implicated in severe renal impairment. This study presents a case analysis that explores the impact of TMEM216 mutations on kidney function and their potential clinical significance.Case presentationWe report a case of a 21-year-old male who developed proteinuria at the age of 15 without an apparent cause. Over the subsequent 6 years, his serum creatinine levels gradually increased, ultimately progressing to ESRD, accompanied by complications such as hypertension and secondary hyperparathyroidism. Imaging studies revealed bilateral renal cysts and a congenital bicuspid aortic valve. Whole-exome sequencing identified compound heterozygous mutations in TMEM216 [c.253C > T (p.R85*) and c.143 T > C (p.L48P)], consistent with an autosomal recessive inheritance pattern. Family analysis indicated that each parent carried one of the mutations. The combination of clinical and genetic findings suggests that the patient’s renal insufficiency may be attributed to TMEM216 mutations, highlighting their potential role in the progression of CKD.ConclusionThis study presents a severe case of renal dysfunction attributed to mutations in the TMEM216 gene, thereby expanding the clinical phenotypic spectrum associated with this gene. Mutations in ciliopathy-related genes may contribute to proteinuria and renal failure by disrupting the polarization and functionality of renal tubular epithelial cells. For young patients with unexplained CKD, genetic testing can serve as an early diagnostic tool to identify the underlying etiology and facilitate personalized treatment strategies. Future research on TMEM216-related nephropathy should aim to further elucidate its pathogenic mechanisms and explore potential therapeutic targets to enhance patient outcomes and advance precision medicine.